The Influence of Cutting Speed and Cutting Initiation Location in Specimen Preparation for the Microtensile Bond Strength Test - Abreu, Celina Wanderley [UNESP]; Santos, Jarbas F. F. [UNESP]; Passos, Sheila Pestana [UNESP]; Michida, Silvia Masae A. [UNESP]; Takahashi, Fernando Eidi [UNESP]; Bottino, Marco Antonio [UNESP] (Quintessence Publishing Co Inc, 2011)
Purpose: This study evaluated the effect of cutting initiation location and cutting speed on the bond strength between resin cement and feldspathic ceramic.Materials and Methods: Thirty-six blocks (6.4 x 6.4 x 4.8 mm) of ceramic (Vita VM7) were produced. The ceramic surfaces were etched with 10% hydrofluoric acid gel for 60 s and then silanized. Each ceramic block was placed in a silicon mold with the treated surface exposed. A resin cement (Variolink II) was injected into the mold over the treated surface and polymerized. The resin cement-ceramic blocks were divided into two groups according to experimental conditions: a) cutting initiation location - resin cement, ceramic and interface; and b) cutting speed - 10,000, 15,000, and 20,000 rpm. The blocks were sectioned to achieve non-trimmed bar specimens. The microtensile test was performed in a universal testing machine (1 mm/min). The failure modes were examined using an optical light microscope and SEM. Bond strength results were analyzed using one-way ANOVA and Tukey's test (alpha = 0.05).Results: Significant influences of cutting speed and initiation location on bond strength (p < 0.05) were observed. The highest mean was achieved for specimens cut at 15,000 rpm at the interface (15.12 +/- 5.36 MPa). The lowest means were obtained for specimens cut at the highest cutting speed in resin cement (8.50 +/- 3.27 MPa), and cut at the lowest cutting speed in ceramic (8.60 +/- 2.65MPa). All groups showed mainly mixed failure (75% to 100%).Conclusion: The cutting speed and initiation location are important factors that should be considered during specimen preparation for microtensile bond strength testing, as both may influence the bond strength results.
Keywords: microtensile bond strength test; cutting speed; ceramic